PERFORMANCE STUDY OF NURSE USING CULTURAL ORGANIZATION APPROACH - Suhartono; Sulistiawati; Esty Yunitasari (NurseLine Journal, 2016)
National problems faced by Indonesia at this time is about the handling of the low quality of human resources (HR). HR issues that need attention in Indonesia is a performance issue. This study aims to determine the effect of individual factors, organizational factors, and factors of organizational culture on performance of nurses. This study using cross sectional study approach and of those samples was determined by simple random sampling technique is 48 nurses ponkesdes Tuban and Lamongan. Theindependent variables in this study is the individual factors (abilities and skills), organizational cultural factors and organizational factors, while the dependent variable is the performance of nurses ponkesdes. The instrument used was a questionnaire and performance assessment sheet. Research analysis using simple linear regression. Test simple linear regressionshowed variable organizational factors have a significant effect on the performance with p value = 0.027, cultural factors organizational statistically signifi-cant effect on performance with p value = 0.000, variable individual factors (abilities